2020
DOI: 10.1101/2020.12.07.414177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutated clones driving leukemic transformation are already detectable at the single cell level in CD34-positive cells in the chronic phase of primary myelofibrosis

Abstract: Disease progression of myeloproliferative neoplasms is the result of increased genomic complexity. Since the ability to predict disease evolution is crucial for clinical decision, we studied single cell genomics and transcriptomics of CD34+ cells from a primary myelofibrosis (PMF) patient who progressed to acute myeloid Leukemia (AML) while receiving Ruxolitinib. Single cell genomics allowed the reconstruction of clonal hierarchy and demonstrated that TET2 was the first mutated gene while FLT3 was the last one… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In this study, we demonstrated that PD-L1 expression was significantly associated with overt myelofibrosis, JAK2V617F, high WBC counts, and HMR mutations as defined by MIPSS70+ in PMF patients. Our findings coincide with a recent report in which PD-L1 expression was increased, along with reduced T-cell activation, during disease progression in a PMF patient, as demonstrated by single cell analysis of hematopoietic stem cells [27]. Likewise, PD-L1 expression has been shown to be an independent prognosis marker in several solid cancers [28][29][30].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we demonstrated that PD-L1 expression was significantly associated with overt myelofibrosis, JAK2V617F, high WBC counts, and HMR mutations as defined by MIPSS70+ in PMF patients. Our findings coincide with a recent report in which PD-L1 expression was increased, along with reduced T-cell activation, during disease progression in a PMF patient, as demonstrated by single cell analysis of hematopoietic stem cells [27]. Likewise, PD-L1 expression has been shown to be an independent prognosis marker in several solid cancers [28][29][30].…”
Section: Discussionsupporting
confidence: 92%
“…One important question is whether these latter leukemias originated from an antecedent clonal hematopoiesis of indeterminate potential (CHIP), different from the one that established the chronic phase MPN. Single cell studies reinforce the extreme complexity and heterogeneity of leukemic evolution in MF with multiple subclones branching from the originating leukemic clone [41,42].…”
Section: Mutational Impact On Disease Phenotype and Therapeutic Respo...mentioning
confidence: 66%
“…Conversely, a positive prognostic effect of CALR mutations has been reported, particularly of type-1 CALR , provided that it is not associated with ASXL1 aberrancy, although the real prognostic impact of CALR subvariants is still controversial in this clinical setting [ 2 , 78 , 79 , 80 ]. More generally, the overall number of mutations frequently increase upon progression and have an impact on outcome [ 12 ]; however, at least some of the mutated clones that effectively drive the transformation may already be present in the chronic phase [ 81 ]. The mutational profiles of MPN-AP and MPN-BP are similar but are markedly different from those of both de novo AML and MPN-CP [ 71 , 82 ].…”
Section: Leukemic Progressionmentioning
confidence: 99%